Ploughshares and Swords : India's Nuclear Program in the Global Cold War - Sarkar, Jayita, 1986- (Book collections on Project MUSE., 2022)
"This book is a study of India's nuclear program (1940s-1980s) through its global partnerships with governments and businesses, its close association with the space program, its anti-nonproliferation stance during most of the Cold War, and the intermestic territorial threats that influenced its unique outcomes"-